PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS MEDIA VIDEO DALAM PEMBELAJARAN IPAS UNTUK MEMOTIVASI BELAJAR SISWA KELAS IV DI SD NEGERI 5 SULAHAN KABUPATEN BANGLI - Desika Yani, Ni Wayan; Arini, Ni Wayan; Suryawan, I Gde (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Video media is considered capable of supporting learning because it presents material visually and attractively, thereby increasing students’ attention during the learning process. However, its use at SD Negeri 5 Sulahan is still dominated by passive watching activities, so students’ activeness and learning motivation have not developed optimally. Therefore, it is necessary to implement a Problem Based Learning model based on video media to encourage students to participate actively in learning activities. This study aimed to describe the implementation of the Problem Based Learning model based on video media, identify the supporting and inhibiting factors, and analyze its impact on the learning motivation of fourth grade students at SD Negeri 5 Sulahan. This study used a descriptive qualitative approach with fourth grade students as the research subjects. Data were collected through observation, interviews, and document studies. The data were analyzed using Miles and Huberman’s interactive analysis techniques consisting of data reduction, data presentation, and conclusion drawing. The results showed that: (1) the implementation of the Problem Based Learning model based on video media in IPAS learning was carried out through planning, implementation, and evaluation stages; (2) the supporting factors included facilities and infrastructure, a conducive learning environment, and positive student responses, while the inhibiting factors included limited learning time, limited facilities, technical obstacles, and the adjustment of problems to students’ abilities; and (3) the implementation of the model had positive impacts on students’ learning motivation, including increased activeness, participation, focus, confidence, and enthusiasm during group discussions and classroom learning activities.